Multilocus sequence typing of Giardia duodenalis genotypes circulating in humans in a major metropolitan area - Hashemi-Hafshejani, Saeideh; Meamar, Ahmad Reza; Moradi, Maryam; Hemmati, Nasrin; Solaymani-Mohammadi, Shahram; Razmjou, Elham (Frontiers in Medicine, 2022)
Giardia duodenalis is an intestinal protozoan parasite of humans and animal hosts and ‎comprises eight microscopically indistinguishable molecularly-diverse lineages ‎designated as assemblages A–H. Assemblages A and B are the primary sources of infections in humans and a wide range of mammals. Here, we identified assemblages, and inter-/intra-assemblage genetic diversity of human G. duodenalis isolates based on the multilocus sequence typing of the triosephosphate isomerase (tpi), β -giardin (bg), and glutamate dehydrogenase (gdh) loci. Multilocus sequence analysis of 62 microscopically-positive G. duodenalis fecal samples identified 26 (41.9%), 27 (43.5%), and nine (14.5%) isolates belonging to assemblages A, B, and discordant assemblages, respectively. The tpi locus assemblage-specific primers identified dual infections with A and B assemblages (45.2%). The sequence analysis of multiple alignments and phylogenetic analysis showed low genetic polymorphism in assemblage A isolates, classified as sub-assemblage AII at three loci, subtype A2 at tpi and gdh loci, and subtype A2 or A3 at bg locus. High genetic variations were found in assemblage B isolates with 14, 15, and 23 nucleotide patterns at tpi, bg, and gdh loci, respectively. Further concatenated sequence analysis revealed four multilocus genotypes (MLG) in 24 assemblages A isolates, two previously-identified (AII-1 and AII-5), with one novel multilocus genotype. However, the high genetic variations observed in assemblage B isolates among and within the three genetic loci prevented the definitive designation of specific MLGs for these isolates. Multilocus sequence typing may provide new insight into the genetic diversity of G. duodenalis isolates in Tehran, suggesting that humans are likely a potential source of G. duodenalis infection. Further host-specific experimental transmission studies are warranted to elucidate the modes of transmission within multiple host populations.